Association between rumination factors and eating disorder behaviours in young women. (2nd January 2016) - Dondzilo, Laura; Rieger, Elizabeth; Palermo, Romina; Byrne, Susan; Bell, Jason
ABSTRACT: Previous research suggests a role for rumination on eating, shape and weight in the maintenance of eating disorder symptoms. The Ruminative Response Scale for Eating Disorders (RRS-ED) measures this type of rumination. To date, no research has verified the two-factor structure of the RRS-ED. Nor has research investigated the association between rumination on eating, shape and weight and the eating disorder behaviours of binge eating and dietary restriction in young adult females. To test these hypotheses, a sample of 119 females (aged 17–24) completed a battery of self-report measures. A confirmatory factor analysis confirmed that the RRS-ED consists of two dimensions, namely reflection and brooding. Furthermore, brooding was found to be uniquely associated with general eating disorder symptoms, over and above mood and body mass index (BMI). Finally, results provided novel evidence for the association between brooding and clinically significant levels of binge eating and dietary restriction, while controlling for mood and BMI. The current study highlights the association between ruminative brooding and eating disorder symptoms in a sample of young adult females. The findings may have implications for prevention and treatment strategies given that binge eating and dietary restraint are primary risk factors for, and also serve to maintain, eating disorders.